2017
DOI: 10.1117/1.jbo.22.3.035010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of shear wave-based elastography techniques in optical coherence tomography

Abstract: We compare five optical coherence elastography techniques able to estimate the shear speed of waves generated by one and two sources of excitation. The first two techniques make use of one piezoelectric actuator in order to produce a continuous shear wave propagation or a tone-burst propagation (TBP) of 400 Hz over a gelatin tissue-mimicking phantom. The remaining techniques utilize a second actuator located on the opposite side of the region of interest in order to create three types of interference patterns:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 42 publications
1
56
0
Order By: Relevance
“…In dynamic OCE, the typical assumption of an infinite, homogeneous, nearly incompressible elastic material would suggest that the elastographic resolution can be described by the OCT image resolution alone, yet, spatial resolution has been reported to range from the micron scale to multiple millimeters for similar reconstruction methods based on elastic wave propagation. [20][21][22][23][24][25][26][27][28] Recently, it was suggested that the mechanical model of the medium is directly related to resolution in the closely related field of compression OCE, 17 thus indicating that spatial resolution is not always defined by the resolution of the imaging method (OCT).…”
Section: Spatial Resolution In Dynamic Optical Coherence Elastographymentioning
confidence: 99%
“…In dynamic OCE, the typical assumption of an infinite, homogeneous, nearly incompressible elastic material would suggest that the elastographic resolution can be described by the OCT image resolution alone, yet, spatial resolution has been reported to range from the micron scale to multiple millimeters for similar reconstruction methods based on elastic wave propagation. [20][21][22][23][24][25][26][27][28] Recently, it was suggested that the mechanical model of the medium is directly related to resolution in the closely related field of compression OCE, 17 thus indicating that spatial resolution is not always defined by the resolution of the imaging method (OCT).…”
Section: Spatial Resolution In Dynamic Optical Coherence Elastographymentioning
confidence: 99%
“…This method is also called the M-B mode acquisition protocol, as described in Ref. 10. Methodologically, in a medium with refractive index n, the phase di®erence ÁðzÞ ¼ ðz; t 1 Þ À ðz; t 0 Þ at two consecutive instants t 0 and t 1 (t 0 < t 1 ), for a given (x o , y o ) position, is related to the particle velocity in the axial direction by…”
Section: Acquisition and Processing Approachmentioning
confidence: 99%
“…9 In particular, a subset of dynamic OCE techniques uses short-duration pulses produced by a selected excitation source in order to produce mechanical wave propagation in the tissue being studied. 10 Excitation sources include acoustic radiation force (ARF), air-pu® excitation, laser-based thermal expansion, and needles connected to piezoelectric vibrators, to name just a few. 11 By tracking the propagating wave, Young's modulus and other biomechanical parameters can be calculated based on the estimation of the wave speed and the selection of the correct wave propagation model dictated by the boundary conditions of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Originally developed for ophthalmic applications to image the posterior segment of the eye [3,[33][34][35] and further enhanced with OCT angiography [36,37], OCT has found successful applications in the anterior segment of the eye [30], as well as in a number of fields, including dermatology [38,39], oncology [40][41][42][43][44][45][46] and dentistry [47]; in endoscopic form it has been applied to cardiology [48,49], gastroenterology [50,51], and pulmonology [52][53][54]. Numerous embodiments of functional OCT [55], including Doppler OCT and polarization-sensitive OCT [56,57], as well as optical coherence elastography [58][59][60][61][62][63][64], multimodal fluorescence-OCT [2,[65][66][67] and spectroscopic OCT [68], have been developed to enhance the structural information obtained with OCT with properties related to tissue function.…”
Section: Applicationsmentioning
confidence: 99%